El método narrativo lúdico para motivar la escritura creativa de cuentos en los estudiantes del tercer año paralelo “A” de la escuela “Ángel Polibio Chaves” de la parroquia Ángel Polibio Chávez, cantón Guaranda, provincia Bolívar, año lectivo 2024-2025. - Fajardo Hurtado, Lady Mariana (2025)
The process of teaching creative story writing can be enhanced through the use of innovative pedagogical strategies such as the ludic narrative method. The literature reviewed underlines the potential of this teaching method in the learning process of children, as it takes advantage of the benefits of gaming techniques in the classroom. Thus, research was conducted to study the topic in depth to propose a series of activities based on this approach with the aim of increasing the motivation for creative story writing through the implementation of the ludic narrative method in students of the third year parallel “A” of the school “Angel Polibio Chaves” of the parish of Angel Polibio Chávez, canton Guaranda, Bolivar province, during the school year 2024-2025. In order to achieve this objective, a mixed methodology that integrated qualitative and quantitative methods was used. Instruments such as questionnaires to be applied to 19 children and the interview to the teacher were used. The results showed that this method is very useful to raise the level of motivation of students in the context analyzed, which led to the design and implementation of a series of activities that enrich the teaching of Spanish.